2021
DOI: 10.1038/s41598-021-83482-9
|View full text |Cite
|
Sign up to set email alerts
|

Brain network motifs are markers of loss and recovery of consciousness

Abstract: Motifs are patterns of inter-connections between nodes of a network, and have been investigated as building blocks of directed networks. This study explored the re-organization of 3-node motifs during loss and recovery of consciousness. Nine healthy subjects underwent a 3-h anesthetic protocol while 128-channel electroencephalography (EEG) was recorded. In the alpha (8–13 Hz) band, 5-min epochs of EEG were extracted for: Baseline; Induction; Unconscious; 30-, 10- and 5-min pre-recovery of responsiveness; 30- a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 78 publications
(112 reference statements)
0
10
0
Order By: Relevance
“…These results are consistent with a previous electroencephalography study, which reported significantly decreased MFS of the classes of open-triangle motif in healthy subjects under anaesthesia compared with those under wakefulness. 66 Thus, both anaesthesia-induced and injury-induced unconsciousness are associated with the topological reorganization of the open-triangle motif between RSNs. In the open-triangle motif, the node connecting to the other two nodes is a relay station for information communication and plays a crucial role in the integration of segregated networks.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with a previous electroencephalography study, which reported significantly decreased MFS of the classes of open-triangle motif in healthy subjects under anaesthesia compared with those under wakefulness. 66 Thus, both anaesthesia-induced and injury-induced unconsciousness are associated with the topological reorganization of the open-triangle motif between RSNs. In the open-triangle motif, the node connecting to the other two nodes is a relay station for information communication and plays a crucial role in the integration of segregated networks.…”
Section: Discussionmentioning
confidence: 99%
“…EEG and EMG changes can serve as valuable indications for measuring transitions between unconscious and conscious state under general anesthesia 3 , 27 . In our study, we utilized the tethered data acquisition system (Medusa, Bio-Signal Technologies, China) to record EEG and EMG signals together with motor activity and behavioural changes of the mice to identify conscious (mixed frequency EEG signals and highly variable muscle tone) and unconscious (continuous slow waves and low EMG signals with high-amplitude sharp waves and/or isoelectric suppression) states 28 , 29 . The signals were amplified, filtered and digitalized with a resolution of 1000 Hz.…”
Section: Methodsmentioning
confidence: 99%
“…Small-world brain organization is, thus, an important feature that facilitates the optimal balance of information segregation and integration required for conscious processing. Studies found that small-world organization is modulated by consciousness state manipulations (i.e., by sleep or anaesthesia) Barttfeld et al, 2015;Uehara et al, 2014;Monti et al, 2013;Schröter et al, 2012), and by consciousness perturbation after brain injury (Duclos et al, 2021;Luppi et al, 2019), further providing empirical evidence that smallworld organization supports conscious information processing. For example, Luppi et al (2019) observed that patients with disorders of consciousness (i.e., in the unresponsive wakefulness syndrome/vegetative state, or the minimally conscious state) displayed reduced small-world characteristics relative to awake healthy volunteers.…”
Section: Introductionmentioning
confidence: 99%